A Cross-sectional Study on the Extended Role of Clinical Pharmacist in Assessing the Risk Factors for Developing Diabetic Foot Ulcers among the Diabetic Patients - Porselvi, A. (Asian Journal of Pharmaceutics (AJP), 2022)
A diabetic foot ulcer (DFU) is the prime cause of poor quality of life among diabetic patients. DFU leads to physical disability and an enormous economic burden on diabetic patients. The development and prognosis of DFU are preventable in most patients by modifying the risk factors for DFU. Programs intervened by clinical pharmacists can enhance rational drugs use and improve the early identification and prevention of DFU. This study intended to prove the beneficial outcome in identifying the risk factors and the provision of patient-tailored referral advice regarding DFU among diabetic patients. This cross-sectional study assessed the neuropathy through Michigan Neuropathy Screening Instrument (MNSI), Monofilament and Vibration test using Tuning Fork and Handheld Doppler for assessing the lower limb vascular disease as per NICE guideline among 137 diabetic patients. 64% of patients were found to have symptoms of neuropathy through the neuropathy assessment test whereas 36% did not have the symptoms. Foot sensory using monofilament test was found to be normal in 49.64% of DFU patients, reduced in 43.80%, and absent in 6.57% of DFU patients. The Ankle Brachial Index (ABI) was found to be normal in 48% of patients, mild in 34% of patients, moderate in 12% of patients, and incompressible in 6% of patients. Clinical Pharmacist intervened risk assessment through Hand-held Doppler, MNSI instrument, and Vibration test helped in screening the DFU patients for Neuropathy, and implementation of effective per patient-tailored education was found to be beneficial in the early identification of DFU and referral to specialty hospitals.